Solutions to reactor system static optimization problems by simulation and control theory methods - Sukharev, A. V.; Golovushkin, B. A.; Labutin, A. N.; Erofeeva, E. V. (Automation and remote control, 2016)
To solve a reactor system static optimization problem by simulation and control theory methods were created a reactor node simulation model and control theory model. The static optimization problem is set and solved.